Sepsis: Antibiotic Resistances of Gram-Positive and Gram-Negative Bacterial in a Tertiary Care Hospital - Siti Nurul Jannah; Muhammad Vitanata Arfijanto; Musofa Rusli; Agung Dwi Wahyu Widodo (Juxta: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2021)
Introduction: Sepsis is a systemic infection that causes multiorgan failure and death. The death rate that is caused by sepsis is increasing. This high value of death has a correlation with the resistance of antibiotics. However, increased antibiotic resistance is not balanced with new research about antibiotics. As a consequence, it causes difficulties in handling sepsis patients who need antibiotic 1-2 hours after diagnosis is enforced.